Effect of Amalaki rasayana on DNA damage and repair in randomized aged human individuals - Vishwanatha, Udupi; Guruprasad, Kanive P.; Gopinath, Puthiya M.; Acharya, Raviraj V.; Prasanna, Bokkasa V.; Nayak, Jayakrishna; Ganesh, Rajeshwari; Rao, Jayalaxmi; Shree, Rashmi; Anchan, Suchitra; Raghu, Kothanahalli S.; Joshi, Manjunath B.; et al. (Journal of ethnopharmacology, 2016)
Preparations from Phyllanthus emblica called Amalaki rasayana is used in the Indian traditional medicinal system of Ayurveda for healthy living in elderly. The biological effects and its mechanisms are not fully understood. Since the diminishing DNA repair is the hallmark of ageing, we tested the influence of Amalaki rasayana on recognized DNA repair activities in healthy aged individuals. Amalaki rasayana was prepared fresh and healthy aged randomized human volunteers were administrated with either rasayana or placebo for 45 days strictly as per the traditional text. The DNA repair was analyzed in peripheral blood mononuclear cells before and after rasayana administration and after 45 days post-rasayana treatment regimen. UVC-induced DNA strand break repair (DSBR) based on extent of DNA unwinding by fluorometric analysis, nucleotide excision repair (NER) by flow cytometry and constitutive base excision repair (BER) by gap filling method were analyzed. Amalaki rasayana administration stably maintained/enhanced the DSBR in aged individuals. There were no adverse side effects. Further, subjects with different body mass index showed differential DNA strand break repair capacity. No change in unscheduled DNA synthesis during NER and BER was observed between the groups. Intake of Amalaki rasayana by aged individuals showed stable maintenance of DNA strand break repair without toxic effects. However, there was no change in nucleotide and base excision repair activities. Results warrant further studies on the effects of Amalaki rasayana on DSBR activities. Amalaki rasayana, an Indian traditional medicine prepared from Phyllanthus emblica is extensively used to maintain health of aged individuals. The present double blind placebo controlled study was carried out in human subjects by following the traditional methods of administration and its ability to influence various DNA repair capacity was analyzed. The results indicate that amalaki rasayana stably maintains UVC induced DNA strand break repair without significantly altering nucleotide excision repair and constitutive base excision repair in aged individuals. The results provide a potential mechanism for the effects of this traditional medicine in aged individuals. [Display omitted]